The Role of Emotional Intelligence in the Work of Executives by Different Anagement Levels - Ganna Rekun; Sofiia Demchenko (Соціальна економіка, 2018)
In modern conditions of globalized society in the theories of management, there is growing attention to emotional information, its importance and the need of its effective use. Researches confirm that emotions can act as organizational resources that can be managed to improve organization’s effectiveness, employee’s performance and create a favorable moral and psychological climate, both within the organization and with external stakeholders. This article studies the main approaches to the application of the concept of «emotional intelligence» among the various levels of management in the organization and offers authors’ development to improve competencies in this area. The relevance of the research is proved, which consists in special attention to the problems of exchange and use of emotional information among personnel and management. The basic competences those are necessary for the development of emotional intelligence from a position of importance for different levels of managers are studied. This article analyzes the development and practices of implementing programs to enhance emotional intelligence in international organizations and corporations. The purpose of the article is to study the influence of emotional intelligence on different levels of managers in order to identify the main areas of competence development. To achieve the set purpose the following tasks have to be solved: to study the concept of «emotional intelligence», its components; to study the basic competences of emotional intelligence; substantiation of competencies and their importance for managers; to research the best practices on increasing the emotional intelligence in organizations and results of its implementation; to analyze the need to apply and develop emotional intelligence among different levels of management. Authors use such research methods as analysis and synthesis, abstraction and generalization, comparison and competency-based approach. The result of the work is developed recommendations for increasing emotional intelligence among executives based on the analysis of the importance of different competencies for different levels of management.